Bibliometric analysis of Indigofera-based natural dyes in the Asia–Pacific: research trends and future directions - Nurul Syazwani Zahari; Siti Fatimah Sabran (Discover Sustainability, 2025)
Abstract Natural dyes have received significant global attention due to concerns about environmental sustainability and human health. Among them, colors generated from Indigofera species have historical and cultural value, and particularly in traditional textile practices in Asia, Africa, and South America. With growing concern about the negative impacts of synthetic dyes, research into plant-based alternatives such as Indigofera has become crucial for producing safer and more environmentally friendly alternatives. This study provides a thorough bibliometric analysis of research on Indigofera-based natural dyes, with a particular emphasis on developments in the Asia-Pacific region. This study includes a bibliometric analysis of 117 Scopus-indexed papers (2000–2024) about Indigofera-based natural dyes. Using VOSviewer, this study identified trends in research output, keyword evolution, and international collaboration networks. The results demonstrate a notable increase in publication activity in recent years, with Indonesia leading the way with 41 publications, followed by India (17), Japan (6), and Malaysia (2). The keyword co-occurrence analysis demonstrates a shift from fundamental chemical research to sustainable, green, and application-driven subjects like antimicrobial textiles and eco-friendly dyeing technologies. The findings highlight Indigofera’s potential as a fundamental contributor to long-term innovation in areas including textiles, cosmetics, biomedicine, and environmental engineering. To optimize its benefits, this study recommends establishing an ASEAN Indigofera Consortium (AIC) to encourage transnational research, maintain traditional knowledge, and foster industrial scalability through eco-innovation.